Intermediate accounting - Welsch, Glenn A.; Newman, D. Paul.; Zlatkovich, Charles T. (Homewood, illinois. Richard D. Irwin, Inc., 1986)
"This Seventh edition continues the leadership role of prior editions in establishing the highest standards of comprehensiveness, academic excellence, and topical presentation. This edition represents a major rewrite rather than a piecemeal revision. The primary emphasis in preparing this revision was to further enhance the text's clarity and conciseness, while maintaining its reputation for technical quality. This textbook is designed primarily for students who have successfully completed a reasonably adequate course in the fundamentals of financial accounting. It is equally adaptable for use by schools that use the semester or the quarter system. Two semester or three quarters or their equivalent normally are required for complete coverage of all chapters."
Includes appendix and index.
English text.
Keywords: Accounting